ANALISIS RETORIKA PRABOWO SUBIANTO DALAM PIDATO DEBAT PEMILIHAN PRESIDEN PADA TAHUN 2019 DAN 2024 - Nawfal Arfa; Septivan Wismo Pratama; Abdullah Faqih Amanullah; Sahda Adillah; Endang Sholihatin Sholihatin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to: 1. find out the rhetoric used by Prabowo Subianto in his 2024 Presidential Election debate speech; 2. Understand Prabowo Subianto's rhetoric in the 2024 Presidential Election compared to his rhetoric in the 2019 Presidential Election; 3. Find out the impact of Prabowo's use of rhetoric in the 2024 presidential election. This research method uses qualitative methods. The conclusions in this research are as follows. 1. The rhetoric used by Prabowo Subianto in his 2024 Presidential Election debate speech is: a strong persuasive style with empathetic and inclusive language, using repetition for emphasis, presenting concrete and relevant examples, and utilizing figurative language and analogies in a more structured sentence structure. 2. Prabowo Subianto's rhetoric in the 2024 Presidential Election compared to his rhetoric in the 2019 Presidential Election, namely: more mature and persuasive, with more empathetic and inclusive language. The argument is more organized, shows greater political maturity, and uses examples that are more relevant to the audience. 3. The impact of Prabowo's use of rhetoric in the 2024 presidential election on society, namely: being able to attract attention and build a positive and inclusive image. The vision and program are easier to understand, potentially increasing support, although there are still weaknesses in the use of hard evidence to support its claims.